Characteristic of Sea Waves Southern Batam City waters-Northen Lingga District waters - Soedrajad Haryo Adji; Risandi Dwirama Putra; Mario Putra Suhana; Try Febrianto; Chandra Joei Koenawan (Journal of Applied Geospatial Information, 2020)
The southern Batam City sea and northern of Lingga District sea are often used by fishing locations and shipping traffic from Batam City to Lingga District. Southern of Batam City sea-northen Lingga District sea have uncertain sea wave conditions that can affect the stability of ship traffic. The purpose of this study is to determine characteristic of sea waves along with wind speed and directions. Characteristic analysis of ocean waves using the SPM (Shore Protection Manual) method from wind direction and speed data in 2018. The height of ocean waves in the northen Batam City sea-southern Lingga District during 2018 is 2.59 meters with periods of 8.47 s up to 0.005 m with a period of 0.39 s. The average wave height in 2018 is 0.69 m with sea wave characteristic patterns still following seasonal wind conditions. The highest sea wave height conditions are in the northern season due to the geographical location of the southern Batam City sea-southern Lingga District sea in the Northern Hemisphere.